SIMULASI PENGECORAN BILLET DENGAN MENGGUNAKAN METODE ELEMEN HINGGA (MS MARC) - Ramang Magga (Program Studi Matematika, Universitas Tadulako, 2009)
This research aim to study the effect of temperature, chilling time, tension, strain, and phase occurred during casting. Finite element simulation method was applied using MS Marc and Fortran software. Condition of casting, when the simulation was run, was divided into three part based on the distance from the center namely 20, 60, and 100 mm. The result showed that simulation at the same temperature, tension of 20 mm has the biggest tension, followed by 60 mm and 100 mm. However, chilling speed at 100 mm from the center was the fastest, and the lowest was 20 mm from the center. At the center of the billet, push tension was occurred. While, pull tension was occurred on the surface